1990
DOI: 10.1149/1.2086580
|View full text |Cite
|
Sign up to set email alerts
|

The Oscillatory Electrodissolution of Copper in Acidic Chloride Solution: I . 0.1M Chloride

Abstract: The electrodissolution of copper in solutions of IN H2SO4 and 0.1M NaC1 is studied. Results were obtained under potentiostatic conditions with a rotating disk anode at 200 and 1000 rpm over the potential range 100-1100 mV vs. a saturated calomel electrode. Potentiostatic current oscillations were observed for 300 mV -< E -< 1050 mV at 1000 rpm while oscillations were observed for 275 mV -< E -650 mV at 200 rpm. We describe the general changes in electrode surface morphology and in the film which covers the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Some researchers in the past have employed electrochemical oscillating signals to study the dynamics of corrosion [6][7][8], where it has been found that these electrochemical signals apparently show chaotic behavior [9][10][11][12][13]; opening an enormous panorama of research, in which it was possible to determine some parameters characteristic of the branch of mathematics called nonlinear system dynamic analysis; among the parameters considered in such studies, the correlation dimension and the maximum Lyapunov exponent were calculated. The work done by Corcoran and Sieradzki [14] is remarkable, for they asserted that the electrochemical oscillating signal during the pitting corrosion phenomenon of silver has chaotic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers in the past have employed electrochemical oscillating signals to study the dynamics of corrosion [6][7][8], where it has been found that these electrochemical signals apparently show chaotic behavior [9][10][11][12][13]; opening an enormous panorama of research, in which it was possible to determine some parameters characteristic of the branch of mathematics called nonlinear system dynamic analysis; among the parameters considered in such studies, the correlation dimension and the maximum Lyapunov exponent were calculated. The work done by Corcoran and Sieradzki [14] is remarkable, for they asserted that the electrochemical oscillating signal during the pitting corrosion phenomenon of silver has chaotic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of copper in 0.5 kmol/m 3 H2SO4 and 0.1 kmol/m 3 NaC1 solutions, Bassett and Hudson (11) showed that the copper surface after 360 oscillations becomes quite rough and porous like the iron surface by SEM image. Therefore, it is considered that the microscopic surface roughness of iron in sulfuric acid also becomes very large under oscillation conditions.…”
Section: Current Oscillationsmentioning
confidence: 98%
“…Moreover, for simplicity, we assume that the reactions are irreversible. The modified equations are as follows X + H20~ g + H + + e- [6] Fe + Y ~Z [7] Z ~ X + U + e- [8] If the rate constants of [6], [7], and [8] are defined as kl, k2, and ka, respectively, and also the rate constants are assumed to be positive, the following rate equations can be derived dX/dt = -k~X + kaZ [9] dY/dt = -kaY + ktX [10] dZ/dt = -kaZ + k2Y [11] where, the ratio of the surface density of Fe atoms to No is unity by the definition of No. Since the H20 concentration change is negligible, k1 is set equal to s k~, where s is the nearly constant water concentration.…”
Section: Chemical Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillations were found in such systems as, e.g., Ni and Fe electrodes in H 2 SO 4 solution [24][25][26][27][28], Cu in HCl [29][30][31], iron in chloride solutions [32], to name just a few. Several theoretical models were formulated that tried to explain oscillating electrodes and chemical oscillations in general [33][34][35].…”
Section: Introductionmentioning
confidence: 99%